Adaptive collaborative management: a value-adding approach to CBFM in the Philippines - Hartanto, H.; Lorenzo, M.C.B.; Valmores, C.; Burton, L.; Arda-Minas, L. (CIFOR and Department of Environmental and Natural Resources (DENR), 2002)
CIFOR conducted a research on Adaptive Collaborative Management (ACM) in two Community Based Forest Management (CBFM) sites in the Philippines for 3 years. This paper describes how different ACM processes were applied at the site level to help the community and local stakeholders in managing their CBFM in a collaborative and adaptive way. As the result of these processes, several changes were noted. These include, among others, increased trust, attitude and awareness among the PO members and different stakeholders, increased skills of PO members, increased communication and information flow within and between stakeholder groups, increased collective action within PO members and across different stakeholders in CBFM implementation, improved feedback mechanisms from local forest managers to decision makers, increased income for PO members, and improved forest resource use and management. This paper concludes by describing how ACM provides adds-on value to the existing CBFM program and putting forward several recommendations to improve CBFM implementation.